FINANCIAL MANAGEMENT BEHAVIOR ON BUY NOW PAY LATER USERS: DOES EDUCATION LEVEL MEDIATES THE EFFECT? - Alfinda Pinky Tamara; Yuli Agustina (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The advancement of digitalization in the modern world has expedited the shift from traditional economies to digital economies, offering both advantages and obstacles. The rapid growth of digital transactions, notably due to the emergence of Buy Now Pay Later (BNPL) services, has sparked worries about its impact on financial management behaviors. As the usage of digital platforms like Shopee PayLater, primarily by Generation Z, continues to increase, there is a critical need to enhance financial literacy and establish self-regulation mechanisms to mitigate the potential risks of excessive consumption. This study examines the relationship found between financial literacy and self-control in financial management behavior using education level as a mediating effect. Generation Z individuals who use Buy Now Pay Later service in Indonesia, namely Shopee PayLater, were targeted as research subjects. This research shows that financial literacy, self-control, and education level each have significantly influenced financial management behavior directly. On the other hand, education level could not mediate the relationship between financial literacy and self-control on financial management behavior since the impact is insignificant. Most Generation Z individuals in Malang, Indonesia who use Shopee PayLater have a high education level, good financial literacy, self-control, and financial management behavior.